Penerapan Model Pembelajaran Kooperatif Tipe Make a Match pada Mata Pelajaran Matematika di Kelas VII SMP Negeri 1 Enam Lingkung - Irmayanti; Zuzano, Fazri; Vermana, Listy (Arden Jaya Publisher, 2024)
This research aims to find out whether the mathematics learning outcomes of students who are taught by applying the make-a match type cooperative learning model are better than the learning outcomes of students who apply ordinary learning in class VII of SMP Negeri 1 Enam Lingkung. This type of research is experimental research. The population in this study were class VII students of SMPN 1 Enam Lingkung. The sample in this study was determined using a random sampling technique (random sample). After carrying out the homogeneity test and average similarity test, the samples selected in this study were class VII.B as the experimental class and class VII.C as the control class. Analysis of student learning outcomes data using the normality test shows that for both the experimental class and the control class, meaning that the learning outcomes of the two sample classes come from samples with a normal distribution. Furthermore, data analysis using the homogeneity of variance test shows that , so the hypothesis is accepted with a real level of so it can be It was concluded that the learning outcome data for the two sample groups had homogeneous variance. Meanwhile, hypothesis testing using the t-test shows that so that means it can be concluded that the hypothesis is rejected. Thus, it can be concluded that the mathematics learning outcomes of students who apply the make a match type cooperative learning model are better than the mathematics learning outcomes of students who use conventional learning at SMP Negeri 1 Enam Lingkung. Keywords: cooperative learning, make a match, mathematics